2020
DOI: 10.1111/jdv.16302
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acne with spironolactone: a retrospective review of 395 adult patients at Mayo Clinic, 2007–2017

Abstract: Background Few large studies have assessed spironolactone treatment of adult female acne. Objectives To explore the role of spironolactone in the treatment of adult female acne. Methods We performed a retrospective case series assessing the efficacy of spironolactone treatment of a cohort of women evaluated at Mayo Clinic in Rochester, Minnesota, from 2007 through 2017. Results In total, 395 patients (median age, 32 years) received a median spironolactone dose of 100 mg daily. Approximately two‐thirds of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
(27 reference statements)
0
12
0
4
Order By: Relevance
“…We have previously reported on the safety and efficacy of spironolactone in the treatment of acne for adult women. 6 The median age of patients in this study was 19 years, which is relatively high for adolescents. This may be due to hesitancy on the part of the parent and/or physician to start an oral medication in younger patients.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…We have previously reported on the safety and efficacy of spironolactone in the treatment of acne for adult women. 6 The median age of patients in this study was 19 years, which is relatively high for adolescents. This may be due to hesitancy on the part of the parent and/or physician to start an oral medication in younger patients.…”
Section: Discussionmentioning
confidence: 76%
“…Response to spironolactone treatment in 80 adolescent patients, stratified according to acne grade As noted in our adult study, blood pressure variations have been previously reported with spironolactone therapy; however, this value was not routinely measured in our practice unless patients noted symptoms of lightheadedness, dizziness, or had concerns regarding low blood pressure. Such symptoms were infrequent in our patient cohort 6. …”
mentioning
confidence: 56%
See 2 more Smart Citations
“… 3 A further case series 4 ( n = 395) advocated the use of spironolactone (100 mg/day) in adult acne. Following a median treatment duration of 13 months, 66.1% of patients had a complete response, and 85.1% had a complete or partial response of > 50% 5 . A positive response to spironolactone was related to a high number of inflammatory lesions at baseline (odds ratio = 1.08; 95% confidence interval 1.03–1.13; P = 0.001) 4 …”
Section: Acnementioning
confidence: 99%